Clinical Features and Complications of the HLA-B27-associated Acute Anterior Uveitis: A Metanalysis. (2nd November 2017) - D'Ambrosio, Enzo Maria; La Cava, Maurizio; Tortorella, Paolo; Gharbiya, Magda; Campanella, Michelangelo; Iannetti, Ludovico
ABSTRACT: In this article, we report a literature-based metanalysis we have conducted to outline the clinical features of the HLA-B27 Acute Anterior Uveitis (AAU). The examined material was based on observational studies in which participants were affected by Acute Anterior Uveitis and divided into HLA B27+ and HLA B27–. We performed a search on articles with the words "HLA B27 uveitis" dated before May 2014. Among these, 29 articles were selected for a second review. After a further evaluation, 22 articles were analyzed. The clinical characteristics studied in the metanalysis were: (1) systemic disease; (2) sex distribution; (3) laterality; (4) visual acuity; (5) hypopion; (6) anterior chamber's fibrin; (7) elevated intraocular pressure (IOP) during inflammation; (8) glaucoma; (9) posterior synechiae; (10) cataract; (11) cystoid macular edema; (12) papillitis. We have calculated a relative risk (RR) for each outcome measured. The results obtained remark some of the peculiar features linked to the HLA B27 Acute Anterior Uveitis, such as strong association with ankylosing spondylitis (RR = 6.80) and systemic diseases (RR = 9.9), male prevalence (RR = 1.2), unilateral (RR = 1.1) or alternating bilateral (RR = 2.2) involvement, hypopion (RR = 5.5), fibrinous reaction and even papillitis (R = 7.7). Simultaneous bilateral (RR = 0.3) AAU is more frequent in HLA-B27 negative form. We report higher risk of elevated IOP and glaucoma (RR = 0.6) in B27– Acute Anterior Uveitis. No significant difference between HLA B 27 positive and negative AAU was observed according to final visual acuity and complications such as posterior synechiae, cataract, and maculare edema. We trust that this will inform on the clinical evaluation and therapeutic decision in addressing a still ill-defined ophthalmologic condition.